Tipología y gestión documental en la televisión temática musical - Caldera Serrano, Jorge (Revista General de Información y Documentación, 2005)
This item describes different documentary types that can found in the musical thematic televisions as well as their main characteristics which allow us to describe and determine their documentary management within the frameg the information systems. For each analyzed documentary type-concert, interview and videoclips —we describen its general and particular elements in order to its conservation and to assure an effective, exhaustive and pertinent recovery, taking into account the potential and actual necessities of the users. For the description of these audio-visual the same elements are used that can appear in other data bases of audio-visual means are used, and this they can be adapted to the kind of informative stuff preserved by other companies
Keywords: Televisión archive / Musical thematic television / Information Management System / Sodund documentation